Comparison of the Anterior Limit of the Dentition in Patients Treated with Self-Ligating Straight-Wire, Conventional Straight-Wire and Standard Edgewise Appliances. (1st July 2012) - Lombardo, Luca; Ficara, Paolo; Maltoni, Ivano; Moser, Lorenz; Guarneri, Maria Paola; Siciliani, Giuseppe
Abstract : The aim of this study was to identify and compare any differences in the position of the anterior limit of the dentition provoked by three different types of orthodontic mechanics: traditional edgewise, straightwire and self-ligating. A sample of 54 patients (selected from a group of 289 patients) possessed a range of Little's Irregularity Index values for the upper and lower dental arches between a minimum of 6.5 and a maximum of 13.5 at T0, and corresponding final values no greater than 2 and hence of minimal irregularity. The 54 patients were subdivided into three groups according to the type of brackets used in their treatment: Group 1 was composed of 24 patients treated using the self-ligating technique, Group 2 of 15 patients treated using a conventional straight-wire technique (Roth) and Group 3 of 15 patients treated using the standard edgewise technique. Cephalometric tracings were performed on laterolateral teleradiography. Group 1 value was found to be nonsignificant, whereas significant labial inclination was noted in Groups 2 and 3 (P < 0.05 ). A significant labial inclination of the upper incisors was also evidenced in all three sample groups.